PENGEMBANGAN MULTIMEDIA INTERAKTIF MATEMATIKA BERMUATAN GAME EDUKASI PADA MATERI BANGUN RUANG KELAS VI SEKOLAH DASAR - Raharjo, Ayu Sholiha Ariyani; Rufi'i, Rufi'i; Hartono, Hartono (Jurnal Teladan: Jurnal Ilmu Pendidikan dan Pembelajaran, 2021)
This study aims to produce interactive multimedia Mathematics containing educational games on appropriate, practical, effective, and interesting spatial building materials. This type of research is Research & Development (R&D) with the model of Lee & Owens (2004). The results of the study found that the analysis of the feasibility level was 79.64% with the "Fair" criteria. The practicality of the product is 89.21% with the criteria of "Very Practical". The attractiveness is 95.41% with the criteria of "Very Attractive". There is an increase in student activity from 24.17% with the "Less" criteria to 85.00% with the "Very Good" criteria so that this multimedia can be said to be effective. The results of this development research indicate that this interactive multimedia of Mathematics is feasible to be used in learning.